Recombinant Bacteroides fragilis enterotoxin-1 (rBFT-1) promotes proliferation of colorectal cancer via CCL3-related molecular pathways - Xie Xiaoliang (De Gruyter, 2021)
Colorectal cancer (CRC) is one of the most frequently diagnosed cancers worldwide and stands among the leading causes of cancer-related deaths. Although deregulation of the microbiota in the gastrointestinal tract has been frequently described in CRC, very little is known about the precise molecular mechanisms by which bacteria and their toxins modulate the process of tumorigenesis and behavior of cancer cells. In this study, we produced recombinant Bacteroides fragilis enterotoxin-1 (rBFT1) and demonstrate that rBFT1 could promote cell proliferation in colorectal cancer cells and accelerate tumor growth in vivo. To identify the mechanisms, we further investigated CCL3/CCR5 and NF-κB pathway. We found that CCL3, CCR5, NF-κB, and TRAF-6 were dramatically upregulated after rBFT1 treatment, thus suggesting that the role of rBFT1 in CRC progression may be associated with CCL3/CCR5 and NF-κB pathways. Collectively, our results indicate that rBFT1 serves as a tumor promoter and plays a crucial role in inducing the proliferation of CRC via accelerating CCL3-related molecular pathway, thus giving insights into mechanistic underpinnings for the prevention and treatment of CRC.